Southeast Europe – unity or cultural diversity - Szulc, Witold; Czamańska, Ilona (Balcanica Posnaniensia. Acta et studia, 2009)
The aim of the article is to present the complex historical processes that led to the development of common cultural elements and strong ethnic and religious divisions in South-Eastern Europe. The analysis covers a wide range of historical sources and examples from different periods – from antiquity, through the Middle Ages, to the 19th and 20th centuries. The authors use a historical-comparative approach, pointing to the continuity and changeability of traditions in the context of political and social transformations. The conclusions indicate that the primary integrating factor in the region was religion, especially Christianity in its two main forms: Orthodox and Latin. The mission of Cyril and Methodius, the development of Slavic alphabets and the liturgy in the Slavic language played a fundamental role in shaping regional identity. On the other hand, political instability, the expansion of nomadic peoples, Islamisation under Ottoman rule, and national and religious rivalries exacerbated divisions. In the modern and contemporary era, alongside universalist ideas aimed at building federal state structures, nationalist movements emerged, which deepened ethnic conflicts. The 20th century brought further resettlements, border changes and attempts to build multinational states, which, however, ended in the ethnic domination of some groups over others.